2019
DOI: 10.1155/2019/9548324
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics (rtx1) High-Resolution Imaging of Photoreceptors and Retinal Arteries in Patients with Diabetic Retinopathy

Abstract: Background. Diabetic retinopathy (DR) is the leading cause of impaired vision in patients with diabetes mellitus. An adaptive optics retinal camera (rtx1™; Imagine Eyes, France) was used to capture images of cones and retinal arteries from patients with DR. Objective. Cone parameters (density, interphotoreceptor distance, and regularity) and retinal artery parameters (wall thickness, lumen diameter, WLR, and WCSA) were analyzed in 36 patients with nonproliferative DR (NPDR; 22 with mild NPDR and 14 with modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 36 publications
(83 reference statements)
9
51
0
1
Order By: Relevance
“…Our study confirmed previous findings of the cone parameters differences between diabetic patients and controls [ 13 - 15 , 22 , 23 ]. Lombardo et al [ 14 ] have studied cone parameters differences at 1.5 degrees eccentricities in DM1 patients with no diabetic retinopathy or nonproliferative diabetic retinopathy and controls.…”
Section: Discussionsupporting
confidence: 93%
“…Our study confirmed previous findings of the cone parameters differences between diabetic patients and controls [ 13 - 15 , 22 , 23 ]. Lombardo et al [ 14 ] have studied cone parameters differences at 1.5 degrees eccentricities in DM1 patients with no diabetic retinopathy or nonproliferative diabetic retinopathy and controls.…”
Section: Discussionsupporting
confidence: 93%
“…However, the lumen and the external diameter was not significantly different. In addition, Zaleska-Zmijewska et al reported that the vessel wall thickness and the WLR in the NDR group was thicker than that of the control group using the images obtained by an AO-camera, but the lumen and the external diameter were not significantly different 16 . Our results confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the increased blood flow is a temporary compensatory mechanism for the reduced blood vessel density to meet the metabolic demand of the photoreceptors. Second, it is known that the photoreceptors are the most oxygen consuming tissue in the retina and the number of photoreceptor is reduced in NPDR 16 . The characteristics would suggest that the more advanced retinopathy led to a greater reduction of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Lombardo and coworkers 44 and Zaleska-Ż mijewska and cowrkers 71 compared the ID of capillaries and large vessels of diabetic retinopathy (DR) patients to healthy controls. Whereas Lombardo and coworkers 44 concluded that the ID of capillaries is 15% narrower in DR patients compared to healthy controls (6.27 μm ± 1.63 vs 7.31 μm ± 1.59, P = 0.002), Zaleska-Ż mijewska and coworkers 71 found no significant difference for arteries (94.2 μm ± 12.2 vs 96.2 μm ± 11.8, P = 0.580) be-tween DR patients and healthy controls; however, an earlier study by Zaleska-Ż mijewska and coworkers 72 did find a significantly smaller ID in prediabetic patients when compared to healthy controls (94.3 μm ± 10.9 vs 105.6 μm ± 14.6, P = 0.022). Furthermore, Gallo and coworkers found a significant correlation between fasting glucose value and arterial and venous ID 20 (r = 0.150, P < 0.001).…”
Section: Outer Diametermentioning
confidence: 99%